Protection barriers used by dentists in Mexico during the COVID-19 pandemic - Franco-Trejo, Christian Starlight (2022)
Objective. Compare the type of protective barriers used in dental clinics in Mexico during the pandemic. Methods. A cross-sectional study was performed with 250 dentists who work in institutions, clinics, or private offices in five states of the Mexican Republic; the information was collected in a Google form that included: informed consent, identification card, use of protection barriers and protocol to use them. A descriptive analysis of the data was prepared. Results. There were 250 participants, 50 from each state, the mean age was 37.10 (SD 11.98), predominating, females, single status and having a bachelor’s degree. The most used barrier was a surgical and/or disposable cap, more than 80% indicated servicing patients using eye protection and a mask; the use of the KN95 / N95 mask was greater than the triple layer, only 3% responded not to use gloves, the use of disposable gowns was high, and 31 participants have not seen patients yet. The majority (48.5%) change hat, face shield, mask, and gown with each patient. They referred to had increased the use of barriers during the pandemic. There was statistical significance between age groups, marital status and educational level with respect to the entity. Conclusions. The use of protective barriers was elevated, the most used equipment was eye protection, face shield, masks, gloves, gown, and disposable fields; however, it is necessary to increase the change of barriers after each patient.